Expression of LhFT1, the Flowering Inducer of Asiatic Hybrid Lily, in the Bulb Scales - Kurokawa, Kana; Kobayashi, Junya; Nemoto, Keiichirou; Nozawa, Akira; Sawasaki, Tatsuya; Nakatsuka, Takashi; Yamagishi, Masumi (Frontiers in Plant Science, 2020)
Asiatic hybrid lily leaves emerge from their bulbs in spring, after cold exposure in winter, and the plant then blooms in early summer. We identified four FLOWERING LOCUS T (FT)-like genes, LhFT1, LhFT4, LhFT6, and LhFT8, from an Asiatic hybrid lily. Floral bud differentiation initiated within bulbs before the emergence of leaves. LhFT genes were mainly expressed in bulb scales, and hardly in leaves, in which the FT-like genes of many plants are expressed in response to environmental signals. LhFT1 was expressed in bulb scales after vernalization and was correlated to flower bud initiation in two cultivars with different flowering behaviors. LhFT8 was upregulated in bulb scales after cold exposure and three alternative splicing variants with a nonsense codon were simultaneously expressed. LhFT6 was upregulated in bulb scales after flower initiation, whereas LhFT4 was expressed constantly in all organs. LhFT1 overexpression complemented the late-flowering phenotype of Arabidopsis ft-10, whereas that of LhFT8 did so partly. LhFT4 and LhFT6 overexpression could not complement. Yeast two-hybrid and in vitro analyses showed that the LhFT1 protein interacted with the LhFD protein. LhFT6 and LhFT8 proteins also interacted with LhFD, as observed in AlphaScreen assay. Based on these results, we revealed that LhFT1 acts as a floral activator during floral bud initiation in Asiatic hybrid lilies. However, the biological functions of LhFT4, LhFT6, and LhFT8 remain unclear.